2022
DOI: 10.3389/fgwh.2022.827365
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions and Experiences of Menstrual Cycle Education and Support in UK Schools

Abstract: The purpose of this study was 2-fold, to (1) explore current education provision in UK schools including barriers to menstrual cycle education and (2) assess the perceived support teachers received to deliver menstrual cycle education. Seven hundred eighty-nine teachers (91% female) from all stages of school education in England (48%), Scotland (24%), Wales (22%) and Northern Ireland (6%) completed an online survey. The survey captured information on menstrual education in schools, teacher's knowledge and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…Our previous research, which surveyed teachers, outlined the lack of education provided in schools across the United Kingdom. Only 63% of primary and secondary teachers reported menstrual education was provided and when it was provided, the primary focus was to teach the biology of the menstrual cycle (56%) or provision of menstrual products (40%) (Brown et al, 2022). The ndings of the present study reveal similar experiences from pupils, providing parallel views between the two groups.…”
Section: Schools Offer a Platform For Educationmentioning
confidence: 51%
See 3 more Smart Citations
“…Our previous research, which surveyed teachers, outlined the lack of education provided in schools across the United Kingdom. Only 63% of primary and secondary teachers reported menstrual education was provided and when it was provided, the primary focus was to teach the biology of the menstrual cycle (56%) or provision of menstrual products (40%) (Brown et al, 2022). The ndings of the present study reveal similar experiences from pupils, providing parallel views between the two groups.…”
Section: Schools Offer a Platform For Educationmentioning
confidence: 51%
“…Speci cally in the United Kingdom, 82% of teachers perceived the menstrual cycle to limit school attendance (Brown et al, 2022). Similarly, a negative effect on school behaviour and participation in Physical Education (PE) were reported by 88% of teachers (Brown et al, 2022). This research is supported by recent reports in which periods have been cited as one barrier to physical activity and PE by adolescents in the UK (YST Girls Active, 2023).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…This fosters open conversations, social support and guidance, and reduces discrimination against menstruating schoolgirls [10]. However, research has shown that teachers lack training and con dence in providing information and a positive environment for students to understand the menstrual cycle beyond a purely biological perspective [11]. In cases where teachers are enthusiastic about assisting students, schoolgirls may always prefer their mothers to be their primary source of information about menstrual hygiene management practices [12], perhaps due to the lack of trust in the school system to assist them without a cause for stigma.…”
Section: Introductionmentioning
confidence: 99%